PENYALURAN KREDIT PT. BANK PERKREDITAN RAKYAT (BPR) MAPALUS TUMATENDEN CABANG TONDANO TERHADAP BIDANG PERTANIAN DI KABUPATEN MINAHASA - Sintia Rompas; Grace A.J. Rumagit; Agnes E. Loho (COCOS, 2016)
ABSTRACTThis study aims to determine the development of their loan portfolio to agriculture, knowing hom to analyze the development and distribution of their loan portfolio to agriculture, as well as knowing how BPR face nonperforming loans during loan repayment. The research was conducted at PT. Bank Perkreditan Rakyat (BPR) Mapalus Tumatenden Branch Tondano in Minahasa by taking some data consumer lending, trade, services, industry and agricultural credit in particular. The data is then finalists by using quantitative and qualitative descriptive analysis presented in tabular from. From the results of this research show that rural banks lending to agriculture decreased in 2012 and then increasing the amount of lending in 2014. Achievement in 2014 is the highest increase in lending over the last 5 years for agriculture. In 2011 through 2015 lending to the agricultural sector can not be found non-performing loans, it can be said that the repayment of credit by the client to the BPR runs smoothly. This is due to good performance of PT. BPR Mapalus Tumatenden Branch Tondano in Minahasa in lending to agriculture intencively with supervision and credit assessment.